Relationship between repeated sprint ability, aerobic capacity, intermittent endurance, and heart rate recovery in youth soccer players - Rodriguez-Fernández, A.; Sanchez-Sanchez, J.; Ramirez-Campillo, R.; Nakamura, Y. F.; Rodriguez-Marroyo, A. J.; Villa-Vicente, G. J. (The Journal of Strength and Conditioning Research, 2019)
To investigate the relationship between repeated sprint ability (RSA) and several aerobic and anaerobic-related soccer-performance indicators, 45 youth soccer players (age 16.8 ± 0.1 years) were classified into "high" (HAF) or "low" aerobic fitness (LAF) (VO2max >= or <60 ml·kg -1·min -1, respectively) and completed an RSA test measuring best (RSAbest), mean (RSAmean), total sprint time (RSAtotal), and percent sprint decrement (Sdec). A laboratory VO2max test (LabTest) together with anaerobic threshold (VT) and peak speed was measured (vLabTest). In addition, a 20-m multistage shuttle run test (MSRT) and a soccer-specific test (TIVRE-Soccer test-TST) were completed. Heart rate (HR) and HR recovery (HRR) were measured during all tests. High aerobic fitness presented greater (p <= 0.05) performance in LabTest, MSRT and TST, at maximal effort, at VT, as well as faster HRR. RSA was similar between HAF and LAF. Contrary to HAF, LAF showed negative correlation between vLabTest with RSAmean (r = -0.6, p = 0.000) and Sdec (r = -0.4, p = 0.044). Also, LAF showed negative correlation between TST end speed (vTST) and RSAmean (r = -0.5, p = 0.005) and Sdec (r = -0.5, p = 0.003). In LAF, RSA was strongly correlated with locomotor factors (e.g., vTST; VT) in both laboratory and field tests. Athletes with high total HRR (>12.5%) in TST presented better (p <= 0.05) Sdec in the RSA test. The multiple regression revealed that the LAF vLabTest explained 44.9, 40.0, and 13.5% of the variance in RSAbest, RSAmean, and Sdec, respectively. Practitioners may consider these findings to optimize youth athletes' assessment and preparation processes.